2016
DOI: 10.17977/um001v1i12016p027
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Letter Sharing Untuk Meningkatkan Keterampilan Komunikasi Siswa Introvert

Abstract: Communication skills are the most important things for teenagers. There is a leaning that the teenagers who have low communication skills can be called as someone who is introvert personality. People who are introvert personality tend to be difficult to communicate and express verbally. The purpose of developing letter sharing media is to improve communication skills of introvert student. This research is development research by adopting Borg and Gall research model. The development result showed that this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…The results of the analysis of the desired teaching material were teaching material consisting of interesting images and following the material. Teaching materials with interesting images will make students more motivated and interested in reading (Afifah et al, 2016;M. R. Cloonan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the analysis of the desired teaching material were teaching material consisting of interesting images and following the material. Teaching materials with interesting images will make students more motivated and interested in reading (Afifah et al, 2016;M. R. Cloonan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…From the results of the analysis of the desired teaching materials are teaching materials consisting of interesting images and in accordance with the material. Teaching materials that have interesting pictures will make students interested and interested in reading (Afifah et al, 2016). In addition, from the results of the needs analysis, it was also found that what students currently need are teaching materials that make it easier for students to understand the material being studied as well as teaching materials found by students in everyday life because that is why.…”
Section: Resultsmentioning
confidence: 98%
“…This is in line with the opinion that mentions things that need to be considered regarding the use of language in the manufacture of electronic teaching materials, namely: (1) the selection of a variety of languages; (2) word selection; (3) the use of effective sentences; (4) the preparation of meaningful paragraphs. This statement is also proven through research results which state that aspects of making electronic teaching materials need to pay attention to the use of language effectively and efficiently, grammatical accuracy, clarity of information, and straightforward language (Afifah et al, 2016;Minawati et al, 2014).…”
Section: Discussionmentioning
confidence: 97%